Impacts of the Great East Japan Earthquake on diabetic patients. Issue 5 (11th March 2015) - Tanaka, Mamiko; Imai, Junta; Satoh, Michihiro; Hashimoto, Takanao; Izumi, Tomohito; Sawada, Shojiro; Uno, Kenji; Hasegawa, Yutaka; Kaneko, Keizo; Yamada, Tetsuya; Ishigaki, Yasushi; Imai, Yutaka; et al.
Abstract Aims/Introduction We investigated impacts of the Great East Japan Earthquake on diabetic patients and characterized those with disaster‐susceptible diabetes. Materials and Methods We enrolled 497 diabetic patients who had been followed at hospitals in devastated areas. We collected metabolic parameters prospectively, 1 and 3 months after the earthquake, and retrospectively for pre‐earthquake time‐points. Questionnaire surveys were carried out regarding earthquake‐related damage and post‐earthquake lifestyle alterations. Available data were analyzed to examine associations with post‐earthquake glycosylated hemoglobin alterations. Results The mean glycosylated hemoglobin level of the participants was not elevated at 1 month, and was significantly decreased at 3 months as compared with the pre‐earthquake glycosylated hemoglobin. There were no significant differences in earthquake‐related damage or lifestyle alterations between the improved and worsened glycemic control groups according to the data obtained from the questionnaire survey. As reported, fasting serum C‐peptide levels were significantly lower in the worsened glycemic control group (P < 0.05). Notably, plasma noradrenaline levels were significantly higher in the worsened glycemic control group (P < 0.05). Furthermore, at 1 month after the earthquake, the plasma noradrenaline level was significantly higher in the low C‐peptide group (fasting serum C‐peptide <1.0 ng/mL) than in the high C‐peptide group (fasting serum C‐peptide ≥1.0 ng/mL), but this difference had disappeared by 3 months after the earthquake. These findings show that post‐earthquake plasma noradrenaline levels were temporarily increased in the low C‐peptide group. Conclusions Sympathetic nerve activation might be elicited more easily in subjects with lower endogenous insulin secretory capacity, and could be involved in the mechanism underlying post‐earthquake worsening of glycemic control.